Developing a web application development MOOC / Z. Zulkifli, S. R. Ismail and I. M. Ibrahim - Zulkifli, Z.; Ismail, S. R.; Ibrahim, I. M. (Universiti Teknologi MARA, Perak, 2018)
Web programming course has been a core courses for students major in computer science. In order to improve the teaching efficiency, a new form of educational delivery referred to as Massive Open Online Courses (MOOC) may represent a promising solution to facilitate better teaching-learning method for improving learning outcomes. In this paper, we proposed a methodology involved in developing the team-based development process of a Web Application Development MOOC, which describes, explains and discusses the basic concept of Internet Technologies, Mark-up Language, Client-Side scripting and Server-Side scripting. This online course consists of 10 modules, corresponding to the 14 weeks of effort in the course taught at the faculty. In addition, we developed various web-based interactive learning and activities modules, which combine the elements of animation, video, audio and graphics to enable the learners to experiment and interact directly with the presented concepts. This online course has been developed using ADDIE methodology, which includes the analysis,design, development, implementation and testing phases.